Peningkatan Pengetahuan Mengenai Perilaku Hidup Bersih dan Sehat Pada Siswa SMAN 16 Pekanbaru - Delidios Delidios; Ami Amelia; Musda Hidayati; Dina Ramsky; Yuharika Pratiwi (Jurnal Pengabdian Ilmu Kesehatan, 2023)
This service aims to increase knowledge about clean and healthy living behavior (PHBS) among students at SMAN 16 Pekanbaru. Knowledge about PHBS is very important to improve the health of individuals and society as a whole through an interactive and participatory approach, researchers and service assistants deliver material that focuses on the importance of personal hygiene, the environment and healthy eating patterns. The results of this service show a significant increase in students' knowledge regarding PHBS. They become more aware of the importance of keeping themselves and their surroundings clean. Apart from increasing knowledge, this service also has a long-term impact by encouraging students to become agents of change in their environment. With the awareness and knowledge gained from this service, it is hoped that SMAN 16 Pekanbaru students will carry out clean and healthy living behavior sustainably and inspire others to do the same.